Exploring the Meaning of University Library Instagram Accounts: Librarian and Users Perspective - Farida, Ida; Wanastri, Prisinta (Insaniyat: Journal of Islam and Humanities, 2025)
This study explores the meaning of two Instagram accounts of Academic Library; the UIN Sunan Kalijaga Yogyakarta and the University of Indonesia, focusing on their posts and engagement. A qualitative phenomenological approach was used to collect data through semi-structured interviews with librarians who manage the accounts and their users who follow the accounts. Instagram has become a central platform for communication and promotion in academic libraries, as evidenced by the University of Indonesia (UI) and UIN Sunan Kalijaga. They use it to share service-related information, document library activities, and encourage student engagement. UI manages its accounts through a centralized system, while UIN uses a collaborative model. However, both institutions emphasize inter-unit coordination and developing librarians' digital design and public communication skills. Despite its potential, Instagram faces several challenges in the library context. These include limited content diversity, low response rates to direct messages, and inadequate visual design skills among account managers. These limitations hinder the platform's ability to meet students' information needs effectively and diminish its capacity to build emotional connections with users. Furthermore, librarians often perceive Instagram as a formal institutional tool, limiting its communicative flexibility and user-centric appeal. To address this, a more humanistic content strategy combining storytelling, an interactive carousel format, and participatory features is needed. This approach would enable more dynamic, two-way communication, increase user engagement, and strengthen the library's image as an inclusive, responsive, and digitally relevant space within the academic community.